THE INFLUENCE OF STORE ATMOSPHERE AND PRODUCT VARIATION ON CUSTOMER SATISFACTION IN KEDAI SEDJAK 2019 MANADO - Prayoga, Vincent; Lapian, S.L.H.V. J; Pandowo, Merinda H. Ch. (Universitas Sam Ratulangi, 2025)
The majority of Indonesians prefer cafes for coffee, with customer satisfaction being vital. Kedai Sedjak 2019 in Manado, with its unique 80s photo studio vibe, excels in store atmosphere but faces challenges like traffic noise and limited air conditioning. Offering a varied menu, including signature drinks like Es Thai Tea and Es Kopi Kedai, it highlights the importance of product variety and innovation in keeping customers satisfied and engaged. Using a quantitative research approach by using Multiple Linear Regression as the method of analysis data. Data was collected through a survey questionnaire distributed to other millennials people who had experienced visited Kedai Sedjak 2019 around 100 sample. The study's findings that the independent variable which are Store Atmosphere and Product Variation have a simultaneous influenced to Online Purchase Decision. This indicates that in Kedai Sedjak 2019 Coffee and Eatery, a welcoming store atmosphere coupled with a diverse range of high-quality products can synergistically enhance customer satisfaction by providing a comfortable environment and offering ample choices to meet varying preferences, ultimately fostering positive experiences and loyalty among patrons. Keyword: Store Atmosphere, Product Variation, Customer Satisfaction